Cardiorenal Signaling Pathways in Heart Failure: Good and Bad News - Rosas-Peralta, Martin; Palomo-Piñón, Silvia; Borrayo Sánchez, Gabriela; Pérez Rodríguez, Gilberto; Ramón Paniagua-Sierra, José (Journal of Hypertension and Cardiology, 2016)
This article reviews heart–kidney signaling in heart failure, contrasting adaptive and maladaptive pathways. It discusses neurohormonal activation, fibrosis, and emerging therapeutic targets.
Keywords: Heart Failure; Heart-Kidney interactions; Cardiorenal syndrome; diastolic dysfunction; inflammation; fibrosis.